Farmer Herders Conflict and the Emergence of Supra-Vigilante Security Measures in Nigeria - Faith Toluwanimi Bella; Ilemobola Peter Olanrewaju (PERSPEKTIF, 2024)
Nigeria has in recent times witnessed increased clashes between farmers and herdsmen in different parts of the country. This has resulted in killings, fighting, and, destruction of both private and public properties. These crises have led to the incessant call for the emergence of vigilante security at the geo-regional level. This paper projects the nexus between the Nigerian government's inability to address the steadily rising farmer-herder crisis that has become a norm and the introduction of vigilante security groups at the geo-regional level. It also analyzes the security challenges in Nigeria and the efforts of these geo-regional securities to curb the crisis. The study is qualitative and secondary sources of data is utilized in analyzing the facet. Recommendation on proper preventive measures for the crisis; a better approach to solidify the relationship between supra-Vigilante groups and the Security agencies; as well as a better security stance in the country will be viewed.